New association between splicing factor‐coding gene polymorphisms and the risk of acute lymphoblastic leukemia in southern Chinese children: A five‐center case–control study. (8th February 2023) - Deng, Decheng; Luo, Ailing; Li, Ming; Yan, Yaping; Cai, Mansi; Liu, Shanshan; Liu, Xiaodan; Wang, Xueliang; Zhang, Xiaohong; Jiang, Hua; Liu, Xiaoping
Abstract: Background: The role of splicing factor‐coding gene polymorphisms in pediatric acute lymphoblastic leukemia (ALL) susceptibility is still unclear. Methods: A case–control designed model was used to estimate the overall risk of pediatric ALL and five single nucleotide polymorphisms (SNPs) of splicing factor‐coding genes in 808 cases and 1, 340 controls, which were genotyped using a TaqMan assay. Stratified analysis was performed to explore the association of rs2233911 genotype and pediatric ALL susceptibility. The influence of splicing factor arginine/serine‐rich 1 (SFRS1) polymorphisms on the sensitivity to different chemotherapeutic regimens based on minimal residual disease (MRD) levels was analyzed. The haplotype analysis was adopted to evaluate the association between inferred haplotypes of the splicing factor‐coding genes and pediatric ALL risk. Results: Among the five analyzed SNPs, SFRS1 rs2233911 AG/GG exhibited a significant association with increased pediatric ALL risk. The stratified analysis further identified the harmful effect of SFRS1 rs2233911 AG/GG in specific subgroups. Moreover, rs2233911 AG/GG had a protective effect on MRD in marrow of ≥0.01%  12 weeks of Chinese Children Cancer Group chemotherapeutics, but provided a harmful effect on MRD in the marrow of ≥0.01% at days 15–19 of the South China Children Leukemia Group chemotherapeutics. Haplotype analysis of these five SNPs yielded haplotypes ACGCC and ACGTC significantly correlating with increased pediatric ALL susceptibility. On the contrary, haplotypes GCATG and GTACC were linked with remarkably decreased pediatric ALL risk. Conclusion: SFRS1 gene polymorphism was associated with increased pediatric ALL risk and indicated that rs2233911 AG/GG might be a potential biomarker for choosing chemotherapeutics. Abstract : A case–control designed model was used to estimate the risk of pediatric acute lymphoblastic leukemia and five SNPs of splicing factor‐coding genes in 808 cases and 1, 340 controls. SFRS1 rs2233911 AG/GG and haplotypes exhibited a significant association with pediatric ALL susceptibility. This figure was created with Biorender.com under academic license.